2018
DOI: 10.3390/en11123385
|View full text |Cite
|
Sign up to set email alerts
|

Performance Analysis of a RED-MED Salinity Gradient Heat Engine

Abstract: A performance analysis of a salinity gradient heat engine (SGP-HE) is presented for the conversion of low temperature heat into power via a closed-loop Reverse Electrodialysis (RED) coupled with Multi-Effect Distillation (MED). Mathematical models for the RED and MED systems have been purposely developed in order to investigate the performance of both processes and have been then coupled to analyze the efficiency of the overall integrated system. The influence of the main operating conditions (i.e., solutions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…In particular, Hu et al [9] reported a maximum exergy efficiency of about 5%, coupling a RED unit with a MED of 10 effects fed with low-grade heat at 95 °C. Palenzuela et al [10] investigated the impact of membrane properties and operating conditions on the integrated system. They reported an exergy efficiency around 7% for the case of real membranes using low-grade heat at 100°C, and up to almost 31% for the case of ideal membranes.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, Hu et al [9] reported a maximum exergy efficiency of about 5%, coupling a RED unit with a MED of 10 effects fed with low-grade heat at 95 °C. Palenzuela et al [10] investigated the impact of membrane properties and operating conditions on the integrated system. They reported an exergy efficiency around 7% for the case of real membranes using low-grade heat at 100°C, and up to almost 31% for the case of ideal membranes.…”
Section: Introductionmentioning
confidence: 99%
“…Hu Junyong [39] , et al analyzed the influence of operating parameters and structural parameters on the system through theoretical models of construction, low temperature multieffect distillation, reverse electrodialysis power generation. Patricia Palenzuela, [40] et al analyzed the performance of RED-MED and Salt Gradient Heat Engine. It is believed that the influence of operating parameters on the overall system is more complex and some favorable operating conditions have been determined.…”
Section: Application Prospect Of Air Gap Diffusion Distillation Technmentioning
confidence: 99%
“…Thermo-osmotic energy conversion based on reverse electrodialysis (RED) has shown particular promise, as it allows operation at relatively low temperatures compared with those of other thermodynamic cycles and does not have any environmental risk [12][13][14][15][16] . RED-based energy conversion is based on charge separation via ion-permeation membranes to convert the chemical potential/temperature gradient into electricity.…”
Section: Introductionmentioning
confidence: 99%